Molecular analysis of clinical Citrobacter spp. isolates: Acquisition of the Yersinia high-pathogenicity island mediated by ICEkp in C. freundii - Zhang, Guangcun; Zhao, Qiang; Ye, Kun; Ye, Liyan; Ma, Yanning; Yang, Jiyong (Frontiers in Microbiology, 2023)
Background. Studies on Citrobacter spp.are limited, hindering our understanding of its species evolution and medical relevance. Methods. A total of 164 clinical Citrobacter spp. isolates were collected from 2017-2020 and identified by VITEK MALDI-TOF MS or VITEK-2 Gram-Negative Identification Card. All isolates were further analyzed by whole-genome sequencing using a HiSeq sequencer. All sequences were processed using different modules of the PGCGAP integrated package: Prokka and fastANI were used for annotation and average nucleotide identification (ANI), respectively. Antibiotic resistance and virulence genes were identified by searching CARD, ResFinder and VFDB databases, respectively. Strains were identified using Ribosomal Multi-locus Sequence Typing (rMLST) classification based on 53 ribosome protein subunits (rps). The evolutionary relationship was analyzed using kSNP3 and visualized by iTOL editor v1_1. Genetic environments were compared by BLAST and visualized by Easyfig 2.2.5. The pathogenicity of some C. freundii isolates was confirmed by Galleria mellonella larvae infection test. Results. A total of14 species of Citrobacter spp. were identified from 164 isolates. However, 27 and 11 isolates were incorrectly identified as C. freundii and C. braakii by MALDI-TOF MS, respectively. In addition, MS also failed to identify C. portucalensis. The virulence genes mainly encoded proteins related to flagella and iron uptake systems. C. koseri isolates (n=28) contained two iron uptake systems, coding yersiniabactin and aerobactin, respectively. C. braakii isolates (n=32), like Salmonella, carried Vi capsule polysaccharide synthesis genes. The yersiniabactin gene clusters identified in five C. freundii isolates are located on various ICEkp elements and have not been reported previously. Moreover, ICEkp-carrying C. freundii showed diverse pathogenic features. Conclusions. Conventional methods have significant defects in identifying Citrobacter spp. . ICEkp-like elements-mediated acquirement of the Yersinia high-pathogenicity island was identified for the first time in C. freundii.